1998
DOI: 10.1191/135245898678919410
|View full text |Cite
|
Sign up to set email alerts
|

Patient perception of quality of care provided by specialists and generalists

Abstract: Efforts to control medical care costs have focused on reducing the number of specialists directing patient care. This cross-sectional survey evaluated multiple sclerosis patient perceptions of the quality of care across three patterns of care: primary care (n = 156), single specialty care (n = 338), and comprehensive care (n = 75). The pattern of medical care received by the patient was defined by: (1) whether the MS provider was a primary care physician or (2) a neurologist; (3) whether the patient reported u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…Der MSQoL-54 wurde auch eingesetzt im Rahmen einer Studie zur Versorgungsqualität von MS-Patienten [88], der SF-36 auch zum Vergleich der LQ und Kosten bei Versorgung von 20 MS-Patienten zu Hause (home based management) oder im Krankenhaus [75]. Bei gleichem Ausgangsstatus ergaben sich deutliche Vorteile der heimischen Versorgung im SF-36 in den Domänen allgemeine Gesundheit, Schmerz, emotionale Rollenfunktion und soziale Funktionsfähigkeit bei geringeren Kosten als bei stationärer Versorgung.…”
Section: Weitere Anwendungen Von Lq-untersuchungenunclassified
“…Der MSQoL-54 wurde auch eingesetzt im Rahmen einer Studie zur Versorgungsqualität von MS-Patienten [88], der SF-36 auch zum Vergleich der LQ und Kosten bei Versorgung von 20 MS-Patienten zu Hause (home based management) oder im Krankenhaus [75]. Bei gleichem Ausgangsstatus ergaben sich deutliche Vorteile der heimischen Versorgung im SF-36 in den Domänen allgemeine Gesundheit, Schmerz, emotionale Rollenfunktion und soziale Funktionsfähigkeit bei geringeren Kosten als bei stationärer Versorgung.…”
Section: Weitere Anwendungen Von Lq-untersuchungenunclassified
“…This rising cost has been argued to have increased the role of primary care physicians, particularly in the US setting (Schwartz 1998). One national comparative study across 13 industrialised countries by Starfield and Shi, (2002) illustrated that strong primary care systems based on a generalist approach work best in terms of equity, access and costeffectiveness.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Two of these papers focussed on patient perceptions of care; Grumbach et al, (1999) and Schwartz et al, (1998), with Diette et al, (2001 conducting a cross-sectional survey to establish whether care for asthma was more consistent with guidelines if specialists or generalists were responsible. Not unsurprisingly Diette et al's., (2001) study found that specialist care for asthma was more consistent with national guidelines for treatment.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Patients treated by MS specialists are more likely to receive MS-related tests and treatment. [1][2][3] Previous studies indicated that most people with MS visit a neurologist at least once a year and that increased contact with a neurologist affects quality of life. [4][5][6] One study found that people with MS rated their MSrelated care as superior when their principal care physician was a neurologist, compared to people with MS whose principal care physician was a medical internist, family or general practitioner, or other physician.…”
mentioning
confidence: 99%
“…1,2,8 This research builds on a previous study identifying urban-rural differences in demographics and disease characteristics among people with MS. 9 The earlier study found significant urban-rural differences in various patient and MS characteristics. That study analyzed differences in demographic and MS characteristics based on location of residence of the person with MS.…”
mentioning
confidence: 99%